An Implementation to Determine the KKM of Music Subject at Junior High School - Utami, Mutiara Arlisyah Putri; Syamsuddin, Syaiful (ETDC: Indonesian Journal of Research and Educational Review, 2022)
A KKM determination is the initial stage of assessment. However, there are still some issues related to the topic, especially in musical some issues related to the topic, especially in music. Therefore, this research used a discrepancy evaluation model to describe the purpose of (1) the implementation level of KKM determination in music, specifically in terms of intake, complexity and carrying capacity. (2) The teachers’ constraints in determining KKM There were six music and art teachers from a junior high school who were taken as subjects in this research. Those subjects were selected using purposive sampling. Data were collected through interviews, documentation, and observations. Data analysis used qualitative analysis and descriptive statistics supported by quantitative data. The results showed that the implementation level of KKM determination in terms of technical procedures was categorized as "good" or "in accordance with predetermined criteria standards." The level of implementation in terms of weighting the value of KKM on the aspect of intake and carrying capacity was categorized as "not very good," while in complexity aspects it was categorized as "good." The teachers’ constraints in determining KKM include: a) determining the value of complexity; b) identifying the student's ability; c) determining the value of the intake; and d) weighing the value of KKM.